2017
DOI: 10.1051/0004-6361/201630338
|View full text |Cite
|
Sign up to set email alerts
|

Optical monitoring of BL Lac object S5 0716+714 and FSRQ 3C 273 from 2000 to 2014

Abstract: Context. Using the 1.56 m telescope at the Shanghai Observatory (ShAO), China, we monitored two sources, BL Lac object S5 0716+714 and flat spectrum radio quasar (FSRQ) 3C 273. For S5 0716+714, we report 4969 sets of CCD (Charge-coupled Device) photometrical optical observations (1369 for V band, 1861 for R band and 1739 for I band) in the monitoring time from Results. The two sources both show IDV properties for S5 0716+714. The timescales are in the range from 17.3 min to 4.82 h; for 3C 273, the timescale is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 78 publications
3
24
0
Order By: Relevance
“…Several authors have reported a similar behaviour to what we have noticed. Agarwal et al (2016) and Yuan et al (2017) notice a very mild trend of larger A var when the source was brighter. Montagni et al (2006) estimated rates of magnitude variation for 102 nights during 1996-2003 for S5 0716+71 and found faster (∼ 0.08/h) rates when source was brighter (R < 13.4), though the dependence was weak, compared to average rate of change (∼ 0.027mag/h) irrespective of the state of the source brightness.…”
Section: Variability Amplitude (Avar) and The Brightness State Of Sourcementioning
confidence: 96%
See 1 more Smart Citation
“…Several authors have reported a similar behaviour to what we have noticed. Agarwal et al (2016) and Yuan et al (2017) notice a very mild trend of larger A var when the source was brighter. Montagni et al (2006) estimated rates of magnitude variation for 102 nights during 1996-2003 for S5 0716+71 and found faster (∼ 0.08/h) rates when source was brighter (R < 13.4), though the dependence was weak, compared to average rate of change (∼ 0.027mag/h) irrespective of the state of the source brightness.…”
Section: Variability Amplitude (Avar) and The Brightness State Of Sourcementioning
confidence: 96%
“…Agarwal et al (2016), during their 130 day study, found a change of about 0.3 mag in spectral color with no significant dependence on the time or brightness phase. Yuan et al (2017) reported a complex pattern for spectral index with time without any specific trend during the period 2000-2014. The color variations are caused by differential cooling of energetic electrons behind the shock front.…”
Section: Spectral Behavior Of S5 0716+71mentioning
confidence: 98%
“…The described change in δ would be reflected on the long-term light curve of the object, which would have prominent peaks. There are no such peaks on the observed light curve (e.g., Raiteri et al 2003;Dai et al 2013Dai et al , 2015Liao et al 2014;Yuan et al 2017;Xiong et al 2020). This could be explained by the fact that other peaks on the light curve are formed by physical processes, but then there is no enough evidence that variability caused by geometrical effects is not superimposed on changes in brightness that are the result of physical processes.…”
Section: Discussionmentioning
confidence: 99%
“…Periodic light curve candidates also include a blazar OJ 287, with 11.5-year period, as the most famous SMBBH candidate [4,5], the quasar PG 1302-102 (6 year period, [29]), the blazar PG 1553+113 (2 year period, [40]), a 13-and 21-year periodicity found in 3C 273 [12,13].…”
Section: Supermassive Black Hole Binariesmentioning
confidence: 99%
“…Unfortunately, most AGN monitoring campaign time intervals are not sufficiently long for detecting periodicity in optical domain of spectra, since expected orbiting time scales in AGN ADs that would affect the optical part of the spectrum are of the order of years and decades. Luckily, significant periodicities are detected in several AGN which are extensively monitored for sufficiently long time, such as OJ287 [4,5], NGC 4151 [6][7][8], NGC 5548 [9,10], Ark 120 [11], 3c273 [12,13].…”
Section: Introductionmentioning
confidence: 99%